Blood pressure and LDL-cholesterol targets for prevention of recurrent strokes and cognitive decline in the hypertensive patient: design of the European Society of Hypertension-Chinese Hypertension League Stroke in Hypertension Optimal Treatment randomized trial - Zanchetti, Alberto; Liu, Lisheng; Mancia, Giuseppe; Parati, Gianfranco; Grassi, Guido; Stramba-Badiale, Marco; Silani, Vincenzo; Bilo, Grzegorz; Corrao, Giovanni; Zambon, Antonella; Scotti, Lorenza; Zhang, Xinhua; et al. (Journal of hypertension, 2014)
BACKGROUND AND OBJECTIVES: The SBP values to be achieved by antihypertensive therapy in order to maximize reduction of cardiovascular outcomes are unknown; neither is it clear whether in patients with a previous cardiovascular event, the optimal values are lower than in the low-to-moderate risk hypertensive patients, or a more cautious blood pressure (BP) reduction should be obtained. Because of the uncertainty whether 'the lower the better' or the 'J-curve' hypothesis is correct, the European Society of Hypertension and the Chinese Hypertension League have promoted a randomized trial comparing antihypertensive treatment strategies aiming at three different SBP targets in hypertensive patients with a recent stroke or transient ischaemic attack. As the optimal level of low-density lipoprotein cholesterol (LDL-C) level is also unknown in these patients, LDL-C-lowering has been included in the design. PROTOCOL DESIGN: The European Society of Hypertension-Chinese Hypertension League Stroke in Hypertension Optimal Treatment trial is a prospective multinational, randomized trial with a 3 × 2 factorial design comparing: three different SBP targets (1, <145-135; 2, <135-125; 3, <125  mmHg); two different LDL-C targets (target A, 2.8-1.8; target B, <1.8  mmol/l). The trial is to be conducted on 7500 patients aged at least 65 years (2500 in Europe, 5000 in China) with hypertension and a stroke or transient ischaemic attack 1-6 months before randomization. Antihypertensive and statin treatments will be initiated or modified using suitable registered agents chosen by the investigators, in order to maintain patients within the randomized SBP and LDL-C windows. All patients will be followed up every 3 months for BP and every 6 months for LDL-C. Ambulatory BP will be measured yearly. OUTCOMES: Primary outcome is time to stroke (fatal and non-fatal). Important secondary outcomes are: time to first major cardiovascular event; cognitive decline (Montreal Cognitive Assessment) and dementia. All major outcomes will be adjudicated by committees blind to randomized allocation. A Data and Safety Monitoring Board has open access to data and can recommend trial interruption for safety. SAMPLE SIZE CALCULATION: It has been calculated that 925 patients would reach the primary outcome after a mean 4-year follow-up, and this should provide at least 80% power to detect a 25% stroke difference between SBP targets and a 20% difference between LDL-C targets.
Keywords: Dementia; Recurrence; hypertenze; Europe; LDL-cholesterol; Ischemic Attack, Transient; kognitivní poruchy; Cholesterol, LDL; China; cévní mozková příhoda; demence; lidé; Evropa; recidiva; Stroke; krevní tlak; statiny; Cognition Disorders; kognice; tranzitorní ischemická ataka; prospektivní studie; sekundární prevence; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Hypertension; Aged; Male; Prospective Studies; Secondary Prevention; Čína; Blood Pressure Determination; Cognition; měření krevního tlaku; Antihypertensive Agents; senioři; mužské pohlaví; antihypertenziva; Blood Pressure; Humans